Greenhouse Screening of the Saprophytic Resident Microflora for Control of Leaf Spots of Wheat (Triticum aestivum) - Perelló, Analía (2001)
Ten microorganisms of the epiphytic microflora of wheat leaves in Buenos Aires Province, Argentina, were evaluated under greenhouse conditions as potential biocontrol agents of the pathogensAlternaria triticimaculans, Bipolaris sorokiniana, Drechslera tritici-repentisandSeptoria triticiin two application sequences (prior to or together with the pathogens). The antagonists significantly reduced the expression of the diseases on wheat plants compared with control plants not inoculated with the antagonists. Maximum percentage of reduction of the necrotic lesion area (NLA) (40–55%) ofS. triticiresulted whenCryptococcussp.,Rhodotorula rubraandPenicillium lilacinwnwere sprayed on leaves prior to inoculations with the pathogen.Bacillussp.,Cryptococcussp.,Fusarium moniliformevar.anthophylium,P. lilacinumandR. rubrareduced significantly (34–52%) the NLA ofB. sorokinianain both of the application sequences. The best antagonistic effect againstA. triticimaculanswas shown byAspergillus niger, Bacillussp.,Chaetomium globosum, F. moniliformevar.anthophyliumandNigrospora sphaerica, with a NLA reduction from 21% to 35% in the co-inoculation or in the sequential application. All microorganisms exceptN. sphaericaperformed better than the control againstD. tritici-repentis. The area under disease progress curve (AUDPC) of the pathogens appeared to progress similarly, but at lower values, in treated plants than in untreated controls. The two yeasts and the bacteria decreased AUDPC to 50–55% ofS. triticiandB. sorokinianacompared with the control in both application sequences, whereas the maximum efficacy againstA. triticimaculanswas reached byN. sphaericaandA. nigerfor the sequential application and byF. moniliformevar.anthophyliumfor the co-inoculation. If the parasitism occurs also in nature, application of antagonists for biological control might provide the opportunity to compete with the pathogens and regulate their colonization in wheat leaves.